Using Nearpod for Teaching Arabic in Kindergarten and Madrasah Ibtidaiyah - Nur Anisah Ridwan; Hanik Mahliatussikah (Universitas Negeri Malang, 2021)
The rapid development of technology lately has had a great influence on various aspects of life, including the world of education. Among them is the creation of various kinds of online learning applications in the form of games. The game application is one of the educational media models that can be used by teachers and students as a learning tool. The use of game applications in the learning process aims in addition to attracting the attention of students to focus more on learning material, it is also intended to create a natural, active and fun learning atmosphere. Thus, it is hoped that students can gain knowledge without feeling forced to learn. This article aims to present the application of the Nearpod game in Arabic learning for vocabulary recognition (mufradat) and basic sentence patterns. Nearpod is a website-based application (accessible on the https://Nearpod.com/ page) that can support the learning process, both offline and online, so that the learning process becomes easy and fun for students.